Data on sand fly fauna (Diptera, Psychodidae, Phlebotominae) in Itatiaia National Park, Rio de Janeiro State, Brazil Dados sobre a fauna flebotomínica (Diptera, Psychodidae, Phlebotominae) do Parque Nacional de Itatiaia, Estado do Rio de Janeiro, Brasil - Margarete M. S. Afonso; Wagner A. Costa; Alfredo C. R. Azevedo; Simone M. da Costa; Maurício L. Vilela; Elizabeth F. Rangel (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
The sand fly fauna in Itatiaia National Park, Rio de Janeiro, Brazil, was investigated in different habitats ranging from sylvatic areas to those altered by human activity related to ecotourism, specifically identifying species that have been suggested as potential leishmaniasis vectors. Sand flies were captured from June 2002 to March 2004, using CDC light traps and Shannon traps. A total of 1,256 sand fly specimens were captured, from species belonging to genera Lutzomyia and Brumptomyia: Brumptomyia guimaraesi, B. troglodytes, Lutzomyia (Lutzomyia) amarali, L. lanei, L. migonei, L. sallesi, L. edwardsi, L. tupynambai, L. (Pintomyia) pessoai, L. (P.) bianchigalatie, L. rupicola, L. (Psathyromyia) shannoni, L. pascalei, L. (Psychodopygus) matosi, L. (P.) davisi, L. (P.) hirsuta hirsuta, L. (P.) ayrozai, L. peresi, L. monticola, and L. misionensis. Worthy of special attention were four species that are considered potential vectors for cutaneous leishmaniasis in Brazil: L. ayrozai, L. hirsuta hirsuta, L. migonei, and L. davisi, representing 19.19% of the specimens captured in this study. A fauna flebotomínica do Parque Nacional de Itatiaia, Rio de Janeiro, Brasil, foi investigada, em diferentes ambientes, envolvendo áreas silvestres e os ambientes ecologicamente alterados, principalmente por atividades ligadas ao ecoturismo, identificando espécies potencialmente vetoras de leishmanioses. As coletas de flebotomíneos foram realizadas no referido parque, no período de junho de 2002 a março de 2004, com armadilhas luminosas do tipo CDC e armadilha de Shannon. Foram coletados 1.256 flebotomíneos, correspondendo às seguintes espécies: Brumptomyia guimaraesi, B. troglodytes, Lutzomyia (Lutzomyia) amarali, L. lanei, L. migonei, L. sallesi, L. edwardsi, L. tupynambai, L. (Pintomyia) pessoai, L. (P.) bianchigalatie, L. rupicola, L. (Psathyromyia) shannoni, L. pascalei, L. (Psychodopygus) matosi, L. (P.) davisi, L. (P.) hirsuta hirsuta, L. (P.) ayrozai, L. peresi, L. monticola e L. misionensis. Merecem especial atenção por sua importância epidemiológica L.ayrozai, L. hirsuta hirsuta, L. migonei e L. davisi, representando 19,19% dos exemplares capturados.